Effects over time of self-reported direct and vicarious racial discrimination on depressive symptoms and loneliness among Australian school students. Issue 1 (December 2017) - Priest, Naomi; Perry, Ryan; Ferdinand, Angeline; Kelaher, Margaret; Paradies, Yin
Abstract Background Racism and racial discrimination are increasingly acknowledged as a critical determinant of health and health inequalities. However, patterns and impacts of racial discrimination among children and adolescents remain under-investigated, including how different experiences of racial discrimination co-occur and influence health and development over time. This study examines associations between self-reported direct and vicarious racial discrimination experiences and loneliness and depressive symptoms over time among Australian school students. Methods Across seven schools, 142 students (54.2% female), age at T1 from 8 to 15 years old (M = 11.14, SD = 2.2), and from diverse racial/ethnic and migration backgrounds (37.3% born in English-speaking countries as were one or both parents) self-reported racial discrimination experiences (direct and vicarious) and mental health (depressive symptoms and loneliness) at baseline and 9 months later at follow up. A full cross-lagged panel design was modelled using MPLUS v.7 with all variables included at both time points. Results A cross-lagged effect of perceived direct racial discrimination on later depressive symptoms and on later loneliness was found. As expected, the effect of direct discrimination on both health outcomes was unidirectional as mental health did not reciprocally influence reported racism. There was no evidence that vicarious racial discrimination influenced either depressive symptoms or loneliness beyond the effect of direct racial discrimination. Conclusions Findings suggest direct racial discrimination has a persistent effect on depressive symptoms and loneliness among school students over time. Future work to explore associations between direct and vicarious discrimination is required.